2013
DOI: 10.1084/jem.20121806
|View full text |Cite
|
Sign up to set email alerts
|

Altered protein prenylation in Sertoli cells is associated with adult infertility resulting from childhood mumps infection

Abstract: Loss of GGPPS from childhood mumps infection or deletion in mice results in constitutively activated MAPK and NF-kB signaling that induces spermatogonium apoptosis, macrophage invasion into seminiferous tubules, and sterility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…[34][35][36][37] Three of the four studies used an RCT study design with low risk for bias, and the fourth used a post-test only design. All four studies found that exposure to the parenting intervention was associated with improved short-term outcomes (i.e., parent-child communication, youth's condom use skills and selfefficacy, communication openness).…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Three of the four studies used an RCT study design with low risk for bias, and the fourth used a post-test only design. All four studies found that exposure to the parenting intervention was associated with improved short-term outcomes (i.e., parent-child communication, youth's condom use skills and selfefficacy, communication openness).…”
Section: Discussionmentioning
confidence: 99%
“…Various infections can also lead to gonadal insufficiency; for example, mumps results in orchitis in select patients. The mechanism leading to decreased fertility is thought to be due to viral infection of the testicular tissue and resultant damage to the Sertoli and Leydig cells as well as testicular atrophy, however this is not completely understood (69)(70)(71). Approximately 13% of patients with mumps orchitis will have resultant subfertility, with infertility in a subset of these patients (71).…”
Section: Other Causes Of Gonadal Dysfunctionmentioning
confidence: 99%
“…These inflammatory factors then bound to the receptors on spermatogonia and activated cell apoptosis signaling pathway, leading to a long-term effect on adult infertility [35,36]. Macrophages could be recruited by chemokines, easily invade the testicular tubules and attack developing spermatogonium cells, resulting in spermatogonia apoptosis [37].…”
Section: The Ras Prenylation and Male Infertilitymentioning
confidence: 99%